Green Extraction Strategies for Sea Urchin Waste Valorization - Marzorati, Stefania; Martinelli, Giordana; Sugni, Michela; Verotta, Luisella (Frontiers in Nutrition, 2021)
Commonly known as “purple sea urchin,” Paracentrotus lividus occurs in the Mediterranean Sea and the eastern Atlantic Ocean. This species is a highly appreciated food resource and Italy is the main consumer among the European countries. Gonads are the edible part of the animal but they represent only a small fraction (10–30%) of the entire sea urchin mass, therefore, the majority ends up as waste. Recently, an innovative methodology was successfully developed to obtain high-value collagen from sea urchin by-products to be used for tissue engineering. However, tissues used for the collagen extraction are still a small portion of the sea urchin waste (<20%) and the remaining part, mainly the carbonate-rich test and spines, are discarded. Residual cell tissues, tests, and spines contain polyunsaturated fatty acids, carotenoids, and a class of small polyphenols, called polyhydroxynaphthoquinones (PHNQ). PHNQ, due to their polyhydroxylated quinonoid nature, show remarkable pharmacologic effects, and have high economic significance and widespread application in several cosmetic and pharmaceuticals applications. A green extraction strategy aimed to obtain compounds of interest from the wastes of sea urchins was developed. The core strategy was the supercritical CO2 technique, characterized by low environmental impacts. Fatty acids and carotenoids were successfully and selectively extracted and identified depending on the physical parameters of the supercritical CO2 extraction. Finally, the exhausted powder was extracted by solvent-based procedures to yield PHNQ. The presence of Spinochrome A and Spinochrome B was confirmed and extracts were characterized by a remarkably high antioxidant activity, measured through the 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay. Overall, the selective and successive extraction methods were validated for the valorization of waste from sea urchins, demonstrating the feasibility of the techniques targeting added-value compounds.